Review of the clinical effectiveness of the neuraminidase inhibitors against influenza B viruses. Issue 11 (November 2013) - Farrukee, Rubaiyea; Mosse, Jennifer; Hurt, Aeron C
Influenza A and B viruses cause significant morbidity and mortality worldwide each year. The neuraminidase inhibitors (NAIs) are the most commonly used class of influenza antiviral drugs for the treatment of infected patients. In vitro studies have shown that influenza B viruses are significantly less susceptible to oseltamivir and other neuraminidase inhibitors compared with influenza A viruses. Following analysis of published clinical studies, we show that oseltamivir does appear to have lower effectiveness in patients infected with influenza B virus compared with influenza A infected patients, but due to insufficient studies on zanamivir, laninamivir or peramivir, it was not possible to conclude the relative effectiveness of these drugs against influenza A virus compared with B virus.